Milho e Brachiaria decumbens em sistemas de integração lavoura-pecuária - Cruz, Simério Carlos Silva [UNESP] (2007)
The search for an ecologically sustainable and economically viable agriculture is growing through the years. Conservation tillages and production systems that aim maximizing soil and water use in a sustainable form, has becoming alternatives, mainly for regions that have relatively short periods of rain and high temperatures. The objective of this research was to evaluate intercropping systems with maize and Brachiaria that has better adaptation to the edaphoclimatic conditions in Zona da Mata region, State of Alagoas. The experiment was conducted in 2005, in the experimental area of Campus Delza Gitaí belonging to the Centro de Ciências Agrárias - CECA, Universidade Federal de Alagoas - UFAL. The treatments consisted of a BRS 3150 hybrid of maize, cultivated in the systems: 1) Conventional Cropping, 2) Minimum Cultivation and 3) No-tillage (BRS 3150 intercropped with Brachiaria decumbens). The randomized block design was used, with subdivided splots and four replications, with an area of 44.8 m2 (6.4 x 7 m) for each subplot. During maize flowering period, it was measured plant height, stem diameter and number of photosynthetic active leaves; for these evaluations... (Complete abstract click electronic access below)